Ensaios em econometria aplicada à segurança alimentar - Moreira, Maria Hosana Pinto (2019)
This dissertation is composed of two chapters, where the first addresses the problem of food insecurity. The central objective is to analyze the food insecurity situation, measured by the Escala Brasileira de Insegurança alimentar - EBIA, and to evaluate the significance of a set of socioeconomic characteristics associated to its occurrence. The analysis uses data from the Pesquisa Nacional por Amostra de Domicílios – PNAD and assesses the incidence of food insecurity in households in rural areas throughout the country. Applying an ordered logit model, the probabilities of households are estimated to be in one of the four food security levels of EBIA. As the literature points out, the analysis showed that per capita household income is the main determinant of the food security situation. The analysis for the years 2004, 2009 and 2013 shows the reduction of food insecurity during the decade considered for rural households. The second chapter has the main objective of evaluating whether the Bolsa Família Program can influence the food security of Brazilian households. As this study also used the PNAD for the year 2013 and because this is a self-reported database, the results obtained therefore deal with the perception of the family itself about its food and nutritional status. To achieve the proposed goal, the propensity score matching technique is used to deal with the non-random selection problem of the program. The results found show significant differences when using clippings between rural and urban regions. In the sample without the cut by area, the PBF does not present statistically significant effects on any level of food insecurity. In urban areas, when considering the effect of PBF on food insecurity at any level, the results were significant, but in an opposite sense. For moderate and severe levels of insecurity, the program showed signs of reducing food vulnerability, but these results were not significant from a statistical point of view. In rural areas, the effects of the estimated PBF corresponded to the expected signal but were statistically significant only on the level of severe food insecurity. Overall, the results indicate that the program should have a better focus among the poorest and most severely food insecure families. This can be confirmed by the results obtained in rural areas, allowing to infer about the importance of the program for this public.